Consensus on current management of endometriosis - Johnson, NP; Hummelshoj, L; World Endometriosis Society Montpellier Consortium (Oxford University Press, 2013)
Study question: Is there a global consensus on the management of endometriosis that considers the views of women with endometriosis?